New ’Young Geographers’ : Children’s Cognitive Development Wayfaring Through the City Replica Project - Black Delfin, Annabelle; Wang, Wenjie (Social Education Research, 2024)
This paper examines how children relate an actual 3D environment to modular, loose parts in creating a 3D city replica with 2D embellishment. The main goals of the study were to examine children’s creation of 3D replicas of immediate physical spaces in their educational setting and the cognitive development that is needed to support this type of play, as well as the cognitive benefits derived from engaging in symbolic 3D construction. Further, this paper explores children’s 2D symbol use in the children’s drawings and marks added to the surfaces of the loose parts during construction play. Framed by Vygotsky’s sociocultural theory (1978), the qualitative research was conducted in a four-year-old classroom at a child development center in the southwest of the United States. Data was collected from photos, participants’ narratives, and fieldwork and analyzed by the photovoice method through a developmental cognitive skills and abilities lens. We observed the interplay of the individual and society reflected in the children’s understanding of their community’s symbolic culture and approach to constructing a city replica. It was found that field trips of neighbourhood walks helped to establish children’s perceptions of their community’s symbolic culture before constructing the city model; further, children have dual representation abilities and can use their abstract reasoning skills in finalizing 3D constructions. Moreover, children used basic spatial skills, such as symbolic representation, position, location, perspective, scaling, direction, and navigation during the city replica 3D construction and in pretend play with the completed city replica product. Lastly, the seminal work of Mitchell (1991) is brought in to ground the results of the research project in the curriculum and pedagogy of early childhood.